Effective assessment in the early years foundation stage - Dubiel, Jan (London : SAGE Publications Ltd, 2016)
"This book is written by one of the leading experts on assessment. It contains the deep knowledge and understanding that comes with knowing a subject inside out; but Jan Dubiel's approach is very practical." -Professor Tina Bruce CBE, University of Roehampton How we assess our youngest children is a vital part of early years practice. The new edition of Jan Dubiel's bestselling book offers a clear explanation of the role of assessment in the revised Early Years Foundation Stage (EYFS), and step-by-step guidance for those working with children from birth to five on making and recording observations in practice. Updated throughout the second edition now features: {u2022} A brand new chapter on the History of the Baseline Assessment Policy {u2022} A companion website including access to SAGE journal articles, child observation videos and examples of completed assessments {u2022} Detailed guidance on the new Integrated Health and Education check at age two This book continues to help students and practitioners develop an evidence-based understanding of assessment and an appreciation of what constitutes effective assessment in early years settings.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Education, Primary; Educational tests and measurements